Geo-mapping of caries risk in children and adolescents - a novel approach for allocation of preventive care - Holmén Anders; Magnusson Kerstin; Strömberg Ulf; Twetman Svante (BMC, 2011)
Abstract Background Dental caries in children is unevenly distributed within populations with a higher burden in low socio-economy groups. Thus, tools are needed to allocate resources and establish evidence-based programs that meet the needs of those at risk. The aim of the study was to apply a novel concept for presenting epidemiological data based on caries risk in the region of Halland in southwest Sweden, using geo-maps. Methods The study population consisted of 46,536 individuals between 3-19 years of age (75% of the eligible population) from whom caries data were reported in 2010. Reported dmfs/DMFS>0 for an individual was considered as the primary caries outcome. Each study individual was geo-coded with respect to his/her residence parish. A parish-specific relative risk (RR) was calculated as the observed-to-expected ratio, where the expected number of individuals with dmfs/DMFS>0 was obtained from the age- and sex-specific caries (dmfs/DMFS>0) rates for the total study population. Smoothed caries risk geo-maps, along with corresponding statistical certainty geo-maps, were produced by using the free software Rapid Inquiry Facility and the ESRI® ArcGIS system. Results The geo-maps of preschool children (3-6 years), schoolchildren (7-11 years) and adolescents (12-19 years) displayed obvious geographical variations in caries risk, albeit most marked among the preschoolers. Among the preschool children the smoothed relative risk (SmRR) varied from 0.33 to 2.37 in different parishes. With increasing age, the contrasts seemed to diminish although the gross geographical risk pattern persisted also among the adolescents (SmRR range 0.75-1.20). Conclusion Geo-maps based on caries risk may provide a novel option to allocate resources and tailor supportive and preventive measures within regions with sections of the population with relatively high caries rates.